2015
DOI: 10.15406/moji.2015.02.00040
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis C with Viral-Suppression linked to Restoration of Innate-Immune Responses with Induction-Therapy with n-IFN-beta followed by Simeprevir

Abstract: Complications associated with hepatitis C virus (HCV) infection may be prevented by viral eradication. Response rates with direct-acting antivirals regimens are generally lower in chronic hepatitis C (CHC) patients who have failed to respond to previous interferon (IFN) treatments. HCV persistence in the host results from in efficient innate and adaptive immune responses. The resolution of a HCV infection may restore impairments in innate and adaptive immunities. Our previous study suggested that induction tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The benefits of IT with CPIT in enhancing RVR and EVR rates may be relevant in treatment strategies involving the combination of IT with CPIT with nIFN-β followed by PR with DAAs in difficult-to treat CHC patients. In our previous study [ 23 ], we demonstrated that a difficult-to-cure patient with HCV genotype 1b, who was a prior null responder to IFN treatments and had chronic active hepatitis with advanced fibrosis was successfully treated by IT with CPIT with nIFN-β followed by PI (simeprevir) with PR, and that these treatments were tolerated well with only mild AEs being noted. The present study showed that the virologic responses rates of IT with CPIT with nIFN-β followed by PI with PR were significantly higher than those of IT with CPIT with nIFN-β followed by PR alone in patients infected with HCV genotype 1b and high viral loads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of IT with CPIT in enhancing RVR and EVR rates may be relevant in treatment strategies involving the combination of IT with CPIT with nIFN-β followed by PR with DAAs in difficult-to treat CHC patients. In our previous study [ 23 ], we demonstrated that a difficult-to-cure patient with HCV genotype 1b, who was a prior null responder to IFN treatments and had chronic active hepatitis with advanced fibrosis was successfully treated by IT with CPIT with nIFN-β followed by PI (simeprevir) with PR, and that these treatments were tolerated well with only mild AEs being noted. The present study showed that the virologic responses rates of IT with CPIT with nIFN-β followed by PI with PR were significantly higher than those of IT with CPIT with nIFN-β followed by PR alone in patients infected with HCV genotype 1b and high viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the restoration of innate immune responses due to viral supression with CPIT during the initial early course of therapy, persistent virologic clearance with triple therapy consisting of protease inhibitor (PI) (simeprevir or vaniprevir) with PR is more likely to result in higher RVR, EVR, ETVR, and SVR. We previously reported that a difficult-to-cure CHC patient with genotype 1b, a high viral load, null response to previous IFN treatments, and advanced hepatic fibrosis was treated by IT with n-IFN-β followed by triple therapy with simeprevir with PR, which resulted in SVR and a sustained biochemical response (SBR) [ 23 ]. On the basis of these findings, we herein compare the efficacies and safeties of CPIT with n-IFN-β as induction therapy followed by triple therapy with PI with PR and CPIT with n-IFN-β followed by PR alone in CHC patients with genotype 1b and high viral loads.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of IT with n-IFN-beta followed by Peg-IFN-alpha and RBV (PR) alone were compared with those of IT plus protease inhibitor (PI) plus PR (NCT with a PI) in patients with CHC with GT 1b and high viral load. IT plus PI and PR is beneficial for treating patients with intractable CHC [12]. CPIT with n-IFN-beta as IT, followed by triple therapy with PI and PR is more effective than IT with n-IFN-beta followed by PR alone in the treatment of patients with intractable CHC with GT 1b and high viral load.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, more effective, tolerable, and/or tailored therapies are required for patients with a prior null response to PR therapy [18]. In addition to the restoration of innate immune responses due to viral suppression with CPIT during the initial early course of therapy, persistent virologic clearance with CPIT followed by triple therapy consisting of PI (Simeprevir or Vaniprevir) with PR is more likely to result in higher RVR, EVR, ETVR, and SVR than those with NCT alone [12]. On the basis of these findings, I treated a patient with CHC with GT 1b, a high viral load, a prior null response to IFN treatments and chronic active hepatitis with advanced fibrosis by using IT with n-IFN-beta followed by triple therapy with Simeprevir (Sovriad ® , Janssen, Titusville, NJ, USA, 100 mg/day per os, daily), Peg-IFN-alpha and RBV, which resulted in SVR and SBR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation